2008
DOI: 10.1074/jbc.m706229200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Protein Geranylgeranyltransferase I and Rab Geranylgeranyltransferase Identified from a Library of Allenoate-derived Compounds

Abstract: Protein geranylgeranylation is critical for the function of a number of proteins such as RhoA, Rac, and Rab. Protein geranylgeranyltransferase I (GGTase-I) and Rab geranylgeranyltransferase (RabGGTase) catalyze these modifications. In this work, we first describe the identification and characterization of small molecule inhibitors of GGTase-I (GGTI) with two novel scaffolds from a library consisting of allenoate-derived compounds. These compounds exhibit specific inhibition of GGTase-I and act by competing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 42 publications
2
76
0
Order By: Relevance
“…Furthermore, the present studies suggest that this behavior of NBD-FPP may be related to an inability to bind the putative second site on RGGT. Recently, another study reported on the identification of novel RGGT inhibitors (25). These inhibitors appear to act via a different mechanism, prob- ably binding to the peptide site as they exhibit competitive kinetics with respect to Rab and uncompetitive kinetics with respect to GGPP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present studies suggest that this behavior of NBD-FPP may be related to an inability to bind the putative second site on RGGT. Recently, another study reported on the identification of novel RGGT inhibitors (25). These inhibitors appear to act via a different mechanism, prob- ably binding to the peptide site as they exhibit competitive kinetics with respect to Rab and uncompetitive kinetics with respect to GGPP.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was determined with Cell Counting Kit-8 -(Dojindo) as described previously (40). Briefly, cells (2.5 × 10 3 for CGL4 and CGL4/gt3) were plated onto 96-well plates and treated with the appropriate inhibitor as indicated in figure legends.…”
Section: Cell Viability Analysismentioning
confidence: 99%
“…That finding prompted both pharmaceutical companies and academic laboratories to develop GGTase-I inhibitors (GGTIs) (26), which have shown promise in preclinical studies (27)(28)(29)(30)(31). The rationale for inhibiting GGTase-I is supported by genetic studies in mice: Inactivating the gene for the ÎČ-subunit of GGTase-I (Pggt1b) reduced tumor formation and prolonged survival in mice with K-RAS-induced lung cancer (32).…”
mentioning
confidence: 99%